2017
DOI: 10.1186/s13578-017-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA GAS5 suppresses pancreatic cancer metastasis through modulating miR-32-5p/PTEN axis

Abstract: BackgroundLong non-coding RNA growth arrest-specific transcript 5 (lncRNA GAS5) is a well-known tumor suppressor in the pathogenesis of a variety of human cancers. The precise role of GAS5 in pancreatic cancer (PC) progression is currently unknown, so the aim of this study was to explore the functional participation of GAS5 in PC metastasis.MethodsThe expression changes of GAS5, miR-32-5p and PTEN in human PC specimens and cell lines were compared by means of molecular biology methods. Transfection of the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 27 publications
3
56
0
Order By: Relevance
“…Study of Tao has found that GAS5 could regulate cardiac fibroblast fibrosis by targeting miR‐21 to regulate PTEN/ MMP‐2 signaling pathway . In pancreatic cancer, GAS5 inhibits metastasis of pancreatic cancer cells by modulating the miR‐32‐5p/PTEN axis . Animal experiments in this study also showed that GAS5 and miR‐21 acted as antitumors by inducing expression of GAS5.…”
Section: Discussionsupporting
confidence: 53%
“…Study of Tao has found that GAS5 could regulate cardiac fibroblast fibrosis by targeting miR‐21 to regulate PTEN/ MMP‐2 signaling pathway . In pancreatic cancer, GAS5 inhibits metastasis of pancreatic cancer cells by modulating the miR‐32‐5p/PTEN axis . Animal experiments in this study also showed that GAS5 and miR‐21 acted as antitumors by inducing expression of GAS5.…”
Section: Discussionsupporting
confidence: 53%
“…GAS5 is one of the few lncRNAs that are negatively correlated with tumor development in breast cancer, malignant pleural mesothelioma and hepatocellular carcinoma (56)(57)(58). GAS5 negatively regulates miR-32-5p to promote the expression of pleiotrophin (PTEN), which can block the activation of the PI3K/Akt signaling pathway, inhibiting the proliferation and survival of PDAC cells (59). Studies have found that GAS5 overexpression can significantly inhibit both the proliferation and invasion of PANC-l and BxPC-3 cells in vitro (60).…”
Section: Gas5mentioning
confidence: 99%
“…Gao et al put forward that GAS5 reduced the drug resistance of cancer cells through regulating MIR‐181c‐5p and Hippo pathway . Moreover, GAS5 could downregulate MIR‐32‐5p and increase the PTEN protein level . SNHG9 was expressed at a lower level in cancer tissues and serum than in normal tissues, and there were negative correlations with cancer stage, lymph node metastasis, disease prognosis.…”
Section: Biological Functions and Mechanisms Of Snhgs In Digestive Camentioning
confidence: 99%